2019
DOI: 10.1136/bmjopen-2019-030576
|View full text |Cite
|
Sign up to set email alerts
|

Needlestick prevention devices: data from hospital surveillance in Piedmont, Italy—comprehensive analysis on needlestick injuries between healthcare workers after the introduction of safety devices

Abstract: ObjectiveNeedlestick and sharps injuries (NSIs) involving healthcare workers (HCWs) are worldwide under surveillance since long time; the implementation of the European Directive 32/2010 regarding the mandatory use of safety-engineered devices (SEDs) seems to have reduced the number of these accidents. Our surveillance investigated the frequency and the modality of SED-related NSIs in the Piedmont region to verify changes in the epidemiology of these events.MethodsWe analysed the exposure records of NSIs, devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
3
19
0
1
Order By: Relevance
“…In our study sample, NSIs in nurses were more often associated with SEDs than NSIs in physicians. Similar results have been reported by other studies, namely that NSIs associated with SEDs were more likely to occur in nurses whereas NSIs in physicians were more likely associated with non-SEDs [ 11 , 20 ]. With the data available to us, we were unable to conclude whether SEDs were less frequently used by physicians than by nurses.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our study sample, NSIs in nurses were more often associated with SEDs than NSIs in physicians. Similar results have been reported by other studies, namely that NSIs associated with SEDs were more likely to occur in nurses whereas NSIs in physicians were more likely associated with non-SEDs [ 11 , 20 ]. With the data available to us, we were unable to conclude whether SEDs were less frequently used by physicians than by nurses.…”
Section: Discussionsupporting
confidence: 90%
“…However, this survey was performed in 2014 and thus only six months after SEDs had become mandatory in Germany. A hospital survey in Italy using routine data for the period from 2014 to 2016 found that 16% of NSIs were associated with SEDs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal MNs are expensive to produce 17 and it has proven difficult to machine hollow metal MNs in a cost effective production process. In terms of width dimensions, the 32G hypodermic needle is similar to the hollow silicon microneedles presented here, but the risk associated with the much increased length of the hypodermic requires continuous training programmes in order to be handled safely, 18,19 and their use results in more pain compared to microneedles. 3 Hollow bevelled silicon microneedles have been demonstrated, 14 but in general their fabrication either relies heavily on wet chemicals such as KOH or HF for the creation of the bevelled surface, 14,[20][21][22] or plasma etching of the bevel surface results in an unconventional needle shape.…”
Section: Introductionmentioning
confidence: 96%